1996
DOI: 10.1103/physrevb.53.4823
|View full text |Cite
|
Sign up to set email alerts
|

Bipolaron lattice formation at metal-polymer interfaces

Abstract: We describe a model for metal-polymer interfaces based on the nondegenerate continuum model of Brazovskii and Kirova for the electronic properties of polymers. The correct analytic equations for a bipolaron lattice in this model are stated and the electronic properties of the bulk polymer, i.e., the energy-level structure, the energy density, and the chemical potential as a function of electron density are obtained numerically. We find that the bipolaron lattice is unstable at high densities when the intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…It is well known that static solutions of the GN model must correspond to reflectionless Schrödinger potentials [7,32]. The fact that the ansatz (27) leads to self-consistency as shown in Refs. [9,10] is therefore quite plausible.…”
Section: ) Physical Originmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that static solutions of the GN model must correspond to reflectionless Schrödinger potentials [7,32]. The fact that the ansatz (27) leads to self-consistency as shown in Refs. [9,10] is therefore quite plausible.…”
Section: ) Physical Originmentioning
confidence: 99%
“…Notice that the simple and intuitive relation between the single baryon and the crystal exhibited in Eq. (29) is hidden in the corresponding Dirac potentials (27) and (5) due to the non-linear relationship between S and U ± .…”
Section: ) Physical Originmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Some of the early studies concentrated on the stability of bipolaron. [6][7][8][9][10] It is now clear that both the electron-phonon coupling and the electron-electron interaction play an important role in forming bipolarons: at low concentration of carriers, carriers are more likely in the form of polarons, while at high concentration of carriers they tend to favor bipolarons. 6 Bipolarons may also coexist with polarons in conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been suggested that the transition from vacuum level alignment to molecular orbital level pinning occurs when the HIB becomes of the same magnitude as the positive polaron relaxation energy. 9,12,13 In this case, charge must be redistributed across the interface, leading to an interface dipole. In other words, the vacuum level is changed but the hole injection barrier stays constant.…”
mentioning
confidence: 99%